2019
DOI: 10.1111/jcmm.14851
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen inhibits cell proliferation by impaired glucose metabolism in gallbladder cancer

Abstract: Gallbladder cancer (GBC) is the leading malignancy of biliary system showing refractory chemoresistance to current first-line drugs. Growing epidemiological evidences have established that the incidence of GBC exhibits significant gender predominance with females two-threefold higher than males, suggesting oestrogen/oestrogen receptors (ERs) signalling might be a critical driver of tumorigenesis in gallbladder. This study aims to evaluate the antitumour activity of tamoxifen (TAM), a major agent of hormonal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Also, Huang et al. recently reported that tamoxifen inhibits the proliferation of gallbladder cancer cells by impairing glucose metabolism ( 52 ). It is known that the occurrence of gall bladder cancer may be related to estrogen receptors suggesting a potential link with the effects of tamoxifen.…”
Section: The Effects Of Hyperglycemia On Tumor Behaviormentioning
confidence: 99%
“…Also, Huang et al. recently reported that tamoxifen inhibits the proliferation of gallbladder cancer cells by impairing glucose metabolism ( 52 ). It is known that the occurrence of gall bladder cancer may be related to estrogen receptors suggesting a potential link with the effects of tamoxifen.…”
Section: The Effects Of Hyperglycemia On Tumor Behaviormentioning
confidence: 99%
“…To formulate ES‐NP (BTZ; Ce6) and encapsulate drugs, BTZ and Ce6 were loaded into the hydrophobic core and self‐assembled with the hydrophilic shell. Due to the high ER expression in GBC (Figure S2 , Supporting Information), the surface‐exposed estrone in the hydrophilic chain act as a tumor‐targeting ligand, [ 10 , 11 , 16 ] whereas the internally packed DA in the hydrophobic chain serves as an ionizable moiety for pH sensitivity. [ 17 ] The use of hydroxyl group as a pH‐sensitive ionizable link between the encapsulated drugs ensures targeted drug delivery at acidic TME, thus lowering drug concentration and avoiding unwanted adverse effects.…”
Section: Resultsmentioning
confidence: 99%
“…ES‐NP (BTZ; Ce6) has various advantages in cancer therapy. For instance, ES acted as a tumor‐targeting ligand in GBC with relatively high ER expression, [ 10 , 11 ] to help nanoparticles rapidly enter the cells and accumulate near the nucleus via ES‐mediated endocytosis or tissue‐specific interactions. [ 12 ] The acidic TME can also be exploited by tumor‐pH‐sensitive nanoparticles for controlled drug release.…”
Section: Introductionmentioning
confidence: 99%
“…In GBCs, glycolysis is a crucial process to support tumor initiation and progression, which could be developed for cancer therapy [19,20]. For instance, the anti-estrogen drug, tamoxifen, suppressed GBC viability by impairing glycolysis [21]. LncRNA PVT1 could modulate glycolysis by regulating miR-143-HK2 to promote GBC growth [19].…”
Section: Discussionmentioning
confidence: 99%